Systematic review of intravenous immunoglobulin in haemolytic disease of the newborn. Issue 1 (1st January 2003) - Gottstein, R; Cooke, R W I
Abstract : Objectives: To assess the effectiveness of high dose intravenous immunoglobulin (HDIVIG) in reducing the need for exchange transfusion in neonates with proven haemolytic disease due to Rh and/or ABO incompatibility. To assess the effectiveness of HDIVIG in reducing the duration of phototherapy and hospital stay. Design: Systematic review of randomised and quasi-randomised controlled trials comparing HDIVIG and phototherapy with phototherapy alone in neonates with Rh and/or ABO incompatibility. Results: Significantly fewer infants required exchange transfusion in the HDIVIG group (relative risk (RR) 0.28 (95% confidence interval (CI) 0.17 to 0.47); number needed to treat 2.7 (95% CI 2.0 to 3.8)). Also hospital stay and duration of phototherapy were significantly reduced. Conclusion: HDIVIG is an effective treatment.